Adaptive crop switching for irrigated agriculture in response to climate change in the Western U.S. - Shahryar Fazli; Wenzhao Li; Surendra Maharjan; Rejoice Thomas; Aqil Tariq; Hesham El-Askary (Agricultural Water Management, 2025)
Adaptive irrigation strategies are crucial for balancing water use, economic viability, and food security in the arid Western United States. However, as a key indicator vital in regulating agricultural productivity and crop irrigation, water use efficiency (WUEc) is becoming increasingly complex to estimate due to climate change. This study explores the critical role of key meteorological drivers, such as maximum temperature (tmax) and vapor pressure deficit (vpd), and their impacts on crop-specific WUEc. Future impacts are also assessed through integrating machine learning models with climate projections from the CMIP6 framework under SSP2–4.5 and SSP5–8.5 scenarios to forecast WUEc trends from 2025 to 2099. Based on WUEc projections, crop-switching strategies were designed to optimize land allocation among cereals in the Imperial Valley and Lower Gila River regions. Results suggest that reallocating cereal crops under SSP2–4.5 can reduce water consumption by up to 13.7 %, while increasing farmers’ profits (up to 44.8 %) and calorie production (up to 2.7 %). Under the warmer SSP5–8.5 scenario, sustaining profit (up to 39 %) and calorie gains (up to 10.2 %) would require up to 9.5 % more water. These findings highlight the importance of crop-switching as a practical adaptation strategy and emphasize the need for region-specific approaches to ensure resilience to climate change. The research underscores the potential of climate-driven decision-making to enhance agricultural sustainability in water-scarce environments.